POLITIK TATA RUANG KOTA DUMAI 2012-2016 - Pertiwi, Rosya Putri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Dumai City is the widest city in Indonesia. But the space in there has not usednicely and feasible. The development in Dumai City still feels minimal perciverd bysociety. Caused by local regulation number 11 in 2002 about Spatial Planning andTerritory(RTRW) in Dumai City valid until 2012. After 2012 until 2016 the new localregulation RTRW Dumai City hasn’t been legales by province government. It caused thedevelopmentinventation that will come to Dumai City obsturcted and needs to wait thenew local regulation to be legaled. The purpose of this research is first, to know theprocess of politic space in Dumai City in 2012-2016. Second, to know the implication ofthe absence of local regulations on Dumai City Spatial Planning and Territory from2012-2016. This tesearch use Policy Theory.The research approach that uses is qualitative approach. The scope, location andtime in this reseach is focused by data that collected by stakeholder in Dumai City in2012-2016. The kind and the research source is divided by primary data with informantakes technique purposively and the secondary data such as the supporting dara aboutRTRW. The collecting data technique used by field research, interview anddocumentation study. While data analysis technique is done by process of reduction,persentation and data verification.The results of the study show that first the process of politic space in Dumai Cityshowed the dynamics of the actor that represent the government, investors, and societycontributed to the inconsistency implementation of RTRW in Dumai City. Second, theimplication of the policy that there is not yet regional regulation on spatial and regionalplans that is Dumai City still dominated by forest and the government in Dumai City can’tgive and issuing building permits, that caused the investation in Dumai City obstrucred.Key words: politic space, policy.